2019
DOI: 10.1167/tvst.8.6.37
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Approach for Meibomian Gland Atrophy Evaluation in Meibography Images

Abstract: Citation: Wang J, Yeh TN, Chakraborty R, Yu SX, Lin MC. A deep learning approach for meibomian gland atrophy evaluation in meibography images. Trans Vis Sci Tech. 2019;8(6):37, https://doi. Purpose:To develop a deep learning approach to digitally segmenting meibomian gland atrophy area and computing percent atrophy in meibography images.Methods: A total of 706 meibography images with corresponding meiboscores were collected and annotated for each one with eyelid and atrophy regions. The dataset was then divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 31 publications
1
57
0
Order By: Relevance
“…In Figure 5 , the NPID approach was compared against the clinical team (clinical meiboscore), the lead clinical investigator (LCI), and a supervised learning approach. 14 The NPID approach achieved 80.9% overall grading accuracy with ImageNet pretrained model, which outperformed the clinical team grading by 25.9% and lead clinical investigator by 1.3%. The NPID approach accuracy without using ImageNet pretrained model was also provided to show that the pretrained model benefited the performance by gaining around 14% accuracy.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…In Figure 5 , the NPID approach was compared against the clinical team (clinical meiboscore), the lead clinical investigator (LCI), and a supervised learning approach. 14 The NPID approach achieved 80.9% overall grading accuracy with ImageNet pretrained model, which outperformed the clinical team grading by 25.9% and lead clinical investigator by 1.3%. The NPID approach accuracy without using ImageNet pretrained model was also provided to show that the pretrained model benefited the performance by gaining around 14% accuracy.…”
Section: Methodsmentioning
confidence: 91%
“…Based on a previous study, 14 University of California, Berkeley Clinical Research Center recruited adult human subjects for a single-visit ocular surface evaluation, which included MG imaging for gland atrophy assessment, during the period from 2012 to 2017. Clinicians used the OCULUS Keratograph 5M (OCULUS, Arlington, WA), a clinical instrument that uses infrared light with wavelength 880 nm for MG imaging 21 to capture MG images of patients’ upper and lower eyelids for both eyes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They evaluate their performance against various clinically relevant metrics and concluded that the automatic segmentation of MGs is very close to the results derived from the ground truth. 16 Developed an algorithm based on the pyramid scene parsing network 17 to segment the MG atrophy regions and eyelid from meibographic images. A dataset composed of 706 meibography images annotated with atrophy regions and eyelid, were used for this study.…”
Section: Introductionmentioning
confidence: 99%